Amyotrophic lateral sclerosis with sensory neuropathy: part of a multisystem disorder?. Issue 7 (15th June 2007) - Isaacs, Jeremy D; Dean, Andrew F; Shaw, Christopher E; Al-Chalabi, Ammar; Mills, Kerry R; Leigh, P Nigel
Abstract : Sensory involvement is thought not to be a feature of amyotrophic lateral sclerosis (ALS). However, in the setting of a specialist motor neuron disease clinic, we have identified five patients with sporadic ALS and a sensory neuropathy for which an alternative cause could not be identified. In three individuals, sensory nerve biopsy was performed, demonstrating axonal loss without features of an alternative aetiology. These findings support the hypothesis that ALS is a multisystem neurodegenerative disorder that may occasionally include sensory neuropathy among its non-motor features.